Can citizen science inform science? Evaluating the results of the Bellingen Riverwatch citizen science program and a complimentary government monitoring program - Dickson, Adrian; Belmer, Nakia; Denshire, Amy; Garland, Ingrid; Lennox, Sue; Ruming, Shane; Lawler, Dominic; Wethered, Adam (Frontiers in Environmental Science, 2024)
In 2015 the sudden decline of the only known population of the Myuchelys georgesi (Bellinger River snapping turtle) triggered a strong community response and a link between turtle mortality and poor water quality in the Bellinger River was suggested. A multi-agency investigation later attributed the mortalities of M. georgesi to a novel virus (the Bellinger River virus) and not a direct effect of poor water quality. However, a lack of consistent water quality or river health data in the catchment limited research of factors that may have heightened susceptibility to the virus or exacerbated its symptoms. Community consultation identified strong connections with the riverine environment and highlighted the cultural, social, economic, and environmental values of the Bellinger River catchment. In 2017 OzGREEN, a not-for-profit environmental education charity based in Bellingen, built upon their existing citizen science water quality monitoring program in collaboration with the Saving our Species (SoS) team in the New South Wales (NSW) Department of Planning and Environment (DPE) who provided funding and equipment, and solicited the involvement of NSW Waterwatch, Western Sydney University and Taronga Zoo. Now known as Bellingen Riverwatch (Riverwatch), the program has become a long-term citizen science program that aims to assist the recovery of M. georgesi, now a critically endangered species, through delivery of monthly water quality data covering the Bellinger River and its tributaries. SoS also engaged the DPE, Estuaries and Catchments Team to commence the Bellinger River Health Program (BRHP) focusing on water quality and aquatic macroinvertebrates to assess river health, with the aim of providing scientifically rigorous data to support the management and recovery of M. georgesi. This case study compares and evaluates the Riverwatch citizen science, and the BRHP professional science, examining methods and results, to compare the accuracy of the citizen science data and assess its reliability for informing ongoing river management. The results demonstrate that Bellingen Riverwatch is a well-managed citizen science program and generally provides valid, accurate and representative results that can be confidently used to enhance the spatial and temporal coverage of the professional science monitoring program.